RANCANGAN KONTEN INFORMATIF SEBAGAI OPTIMALISASI WEBSITE CILETUH PALABUHANRATU UNESCO GLOBAL GEOPARK, KECAMATAN CIEMAS, KABUPATEN SUKABUMI - Krisna, Allysa Putri (STAH Dharma Sentana Sulawesi Tengah, 2025)
Ciletuh-Palabuhanratu UNESCO Global Geopark (CPUGGp) is the only geopark in West Java that features geotourism attractions, including waterfalls, coastal geosites, and unique geological phenomena. However, the optimization of information dissemination through the official website (ciletuhpalabuhanratugeopark.id) remains suboptimal, making the region's attractions less well-known. This research aims to design informative content for the CPUGGp website to optimize the existing official website. The approach combines the Design Thinking and Multimedia Development Life Cycle (MDLC) methods. Design Thinking is applied to understand user needs through the stages of empathize, define, ideate, prototype, and testing, while MDLC is used to design and implement the website prototype through six stages: concept, design, material collecting, assembly, black box testing, and distribution. The integration of these two methods allows the research to produce a user-centered, multimedia-based technological solution.